Museums in Ghana: Visitor Education, Experiences and Satisfaction - Amoako-Hene, Kwasi; Nortey, Samuel; Bodjawah, Edwin Kwesi (International Journal of Culture and Art Studies, 2022)
Patronage and visitor education has been of great concern to the management of museums in Ghana. The need to assess visitors' experience, education, and satisfaction to inform policy is expedient. This study looked at visitor experience and satisfaction with museum education in Ghana. Visiting and studying nine museums under the Ghana Museums and Monument Board (GMMB) and using both qualitative and quantitative approaches, the study revealed that visitor experiences, satisfaction, and education are unsatisfactory. There are issues with teaching methods, the state of exhibits and exhibition styles, and the challenge of low possibility for visitor revisit. Results show that there are low innovative educational and entertaining activities to strengthen museum infrastructure. There is a need to commit resources to strengthen museums and introduce activities that would serve as grounds for museum learning. A strong engagement of visitor education in a positive, socio-cultural and conducive learning atmosphere is very much expedient.